(untitled) (Web of Teachers: Inderscience Research, 2025)
One of the key tasks of the modern education system is to develop professional skills and competencies in future teachers. This article examines the role and significance of professional reflection in shaping transversal competencies among prospective teachers. It theoretically and practically proposes contemporary methods for training pedagogical staff based on professional reflection and highlights ways to enhance the effectiveness of preparing specialists with transversal competencies. Furthermore, the study explores advanced pedagogical technologies and their integration into the process of professional reflection.